Steroid Cell Tumor of the Ovary in an Adolescent: A Rare Case Report - Gokhan Boyraz; Ilker Selcuk; Zarife Yusifli; Alp Usubutun; Serdar Gunalp (Case Reports in Medicine, 2013)
Steroid cell tumors (SCTs) of the ovary are a rare subgroup of sex cord tumors, account for less than 0.1% of all ovarian tumors, and also will present at any age. These tumors can produce steroids, especially testosterone, and may give symptoms like hirsutism, hair loss, amenorrhea, or oligomenorrhea. For the evaluation of androgen excess, testosterone and dehydroepiandrosterone sulfate (DHEA-S) are the first laboratory tests to be measured. A pelvic ultrasound and a magnetic resonance imaging are useful radiologic imaging techniques. Although steroid cell tumors are generally benign, there is a risk of malignant transformation and clinical malignant formation. Surgery is the most important and hallmark treatment.